The Chemistry of Alkali Metals: Properties, Reactions, and Applications - Bakhriddinova Dilnora Sharifjon kizi; Abdunazarov Shoxzodbek Utkirjon ugli; Rabbimov Elmurod Farhod ugli (Peerian Journals Publishing, 2023)
This article provides an overview of the chemical properties of alkali metals, including their reactivity, solubility, and unique atomic structures. It could also discuss how these properties make alkali metals useful in a range of applications, from medicine to agriculture.
Keywords: Alkali metals; atomic structure; Electron configuration